Pengaruh Konsentrasi Ekstrak Teripang Emas (Stichopus hermanni) terhadap Aktivitas Antioksidan Nanoemulsi Minyak Biji Anggur (Vitis vinifera) - Siti Umroh Noor; Amelia Gozali (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Gold sea cucumber extract (Stichopus hermanni) is rich in collagen and unsatturated fatty acid also known omega 3 such as docosahexaenoic acid and eicosapentaenoic acid that highly effective as an antioxidant. Oligomeric proanthocyanidin is the main content in grape seed oil and the most powerful antioxidant agent that can protect collagen. The aim of research was to determine the effect of gold sea cucumber extract concetration on antioxidant activity of grape seed oil nanoemulsion. The three formulas with results test of antioxidant activity with DPPH method using 15% Brij CS12® and 30% propylene glycol has done which the oil phase was dispersed in the aqueous phase.Variation that have been done is to use the antioxidant activity (IC50) of gold sea cucumber extract for 2, 4, and 6 times. The resulting preparations was conformed of organoleptic, nanoemulsion type, clarity, globule size, viscosity and rheology, pH and freez thaw test. Antioxidant activity of gold sea cucumber extract and grape seed oil were (IC50= 53.79 and 17.41 μg/mL respectively). The nanoemulsion was analysed using two-way ANOVA method. Antioxidant activity at storage for 0; 2 and 4-weeks of formula I, II, III were (IC50= 49.15; 49.45, 51.15 µg/mL), (IC50= 44.12, 47.48, 48.14 µg/mL), and (IC50= 42.14, 43.45, 45.33 µg/mL) respectively. Can be concluded that the higher concentration of gold sea cucumber extract, the antioxidant activity of nanoemulsion is higher, but it decreased during the storage.